2018
DOI: 10.1007/s11596-018-1930-1
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Differential Genes in Thoracic Spinal Cord Involved in Experimental Cholestatic Itch Mouse Model

Abstract: The spinal origin of cholestatic itch in experimental obstructive jaundice mouse model remains poorly understood. In this study, the jaundice model was established by bile duct ligation (BDL) in mice, and differential gene expression patterns were analyzed in the lower thoracic spinal cord involved in cholestatic pruritus after BDL operation using high-throughput RNA sequencing. At 21st day after BDL, the expression levels of ENSRNOG00000060523, ENSRNOG00000058405 and ENSRNOG00000055193 mRNA were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Rapid advancements in high-throughput technologies and computational frameworks offer an excellent opportunity to quantify spinal nociception using neuronal activation induced by noxious stimuli. The author's previous study showed that transcriptomics and metabolomics enable the examination of spinal biological systems in unprecedented detail (32)(33)(34)(35)(36). More recently, different patterns were revealed in the metabolic and transcriptional levels of the thoracic spinal cord under myocardial ischemia-reperfusion injury (37)(38)(39).…”
Section: Quantitative Proteomics Reveal the Alterations In The Spinalmentioning
confidence: 99%
“…Rapid advancements in high-throughput technologies and computational frameworks offer an excellent opportunity to quantify spinal nociception using neuronal activation induced by noxious stimuli. The author's previous study showed that transcriptomics and metabolomics enable the examination of spinal biological systems in unprecedented detail (32)(33)(34)(35)(36). More recently, different patterns were revealed in the metabolic and transcriptional levels of the thoracic spinal cord under myocardial ischemia-reperfusion injury (37)(38)(39).…”
Section: Quantitative Proteomics Reveal the Alterations In The Spinalmentioning
confidence: 99%
“…It has been revealed that long non-coding (lnc)RNAs serve a key role in the processing of gene expression signals via the regulation of cell cycle distribution, stem cell differentiation and transcriptional and post-transcriptional control (19,20). Moreover, there are aberrant expression levels of spinal lncRNAs in peripheral diseases, such as pruritus (21,22), acute kidney injury (23), neuropathic pain and inflammation-related pain (24).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the mechanism of pruritus in the presence of cholestasis and thus to evaluate the effectivity of therapeutic drugs, animal models are needed. Several rodent models of cholestasis have been established by drug treatment, 9,10) surgery, 11,12) and genetic manipulation. 13) Among them, mice with surgically-induced cholestasis more closely mimicked the human disease.…”
Section: Introductionmentioning
confidence: 99%
“…9,10,13) Recently, a mouse model of cholestatic pruritus induced by common bile duct ligation (BDL) was reported, 11) although its life time was short. 11,12) Since the severity of cholestatic pruritus is associated with chronic progression of cholestasis, long-term survival of the mouse model is required in order to develop the most effective treatment. Therefore, in this study, we developed a new cholestatic pruritus mouse model induced by BDL and evaluated its treatment with several anti-pruritic drugs.…”
Section: Introductionmentioning
confidence: 99%